Preparation Of Simplicia And Testsspecific And Non-Specific Parameters Of Celery Mustard (Cyanthilium Cinereum) - Imalia Tiranda; Heldi Candra (International Journal of Social Science, 2026)
Sky mustard (Cyanthillium cinereum) is a medicinal plant that has long been used in traditional medicine because of its potential pharmacological properties attributed to its bioactive secondary metabolites. Standardization of simplicia is essential to ensure the quality, safety, and consistency of herbal raw materials prior to their utilization in pharmaceutical preparations. This study aimed to prepare sky mustard simplicia and evaluate its specific and non-specific quality parameters as well as its phytochemical characteristics. A laboratory-based experimental study was conducted using sky mustard leaves processed into simplicia through harvesting, wet sorting, washing, drying, grinding, and storage. Ethanolic extracts were prepared using maceration followed by Soxhlet extraction. Quality evaluation included determination of moisture content, drying loss, total ash content, water-soluble extractive value, ethanol-soluble extractive value, and thin-layer chromatography (TLC). The results demonstrated that the water-soluble extractive value (19.1%) and ethanol-soluble extractive value (6%) met the requirements of the Indonesian Herbal Pharmacopoeia. However, the moisture content (18%), drying loss (42%), and total ash content (20%) exceeded the recommended standards, indicating that improvements in the drying and post-harvest handling processes are required. Thin-layer chromatography revealed characteristic chromatographic profiles with Rf values of 0.7125, 0.8150, and 0.9625, confirming the presence of bioactive constituents. These findings indicate that Cyanthillium cinereum has promising potential as a herbal medicinal material, although optimization of simplicia preparation and standardization procedures is necessary to obtain consistent quality and comply with pharmacopoeial standards